The Burden of the Pain: Adverse Mental Health Outcomes of COVID-19 in Women With and Without Cancer - Lanzoni, Lucilla; Brivio, Eleonora; Oliveri, Serena; Guiddi, Paolo; Chichua, Mariam; Mazzocco, Ketti; Pravettoni, Gabriella (Frontiers in Psychology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic had a negative psychological impact on the population at scale, yet it is possible that vulnerable patient populations may experience a heavier burden with increased feelings of anxiety and distress. Cancer patients have to trade-off between the fear of exposing themselves to the virus and the need to continue life-saving medical procedures. The present study investigated the prevalence of generalized anxiety and post-traumatic stress symptoms (PTSS) in a population of Italian cancer patients and healthy participants in the months following the COVID-19 outbreak. Using standardized measures of PTSS (Impact of Event Scale Revised; IES-R) and generalized anxiety (Generalized Anxiety Scale; GAD-7), we found that patients experienced higher levels of adverse mental health outcomes. Several variables were found to negatively affect PTSS and anxiety in this population, including the younger age of respondents, having children, and the impossibility to attend regular medical check-ups. These findings stress the importance of maintaining a clear and regular communication with patients throughout future waves of the pandemic, and ensure continuity of care in this vulnerable population. Furthermore, this study indicates the need to establish psychological interventions aimed at patients with cancer, targeting especially younger generations who are more likely to experience adverse psychological outcomes.